MODELS OF FATIGUE LIFE CURVES IN FATIGUE LIFE CALCULATIONS OF MACHINE ELEMENTS – EXAMPLES OF RESEARCH - Grzegorz SZALA; Bogdan LIGAJ (Scientific Journal of Silesian University of Technology. Series Transport)
In the paper there was attempted to analyse models of fatigue life curves possible to apply in calculations of fatigue life of machine elements. The analysis was limited to fatigue life curves in stress approach enabling cyclic stresses from the range of low cycle fatigue (LCF), high cycle fatigue (HCF), fatigue limit (FL) and giga cycle fatigue (GCF) appearing in the loading spectrum at the same time. Chosen models of the analysed fatigue live curves will be illustrated with test results of steel and aluminium alloys.